Clinical effect of rhubarb on the treatment of chronic renal failure: A meta-analysis - Huang, Wei; Rao, Yanling; Li, Liang; Li, Chengyin; An, Yi (Frontiers in Pharmacology, 2023)
Objective: To evaluate the benefits of Rhubarb in the treatment of chronic renal failure (CRF) by conducting a meta-analysis. Methods: The randomized and semi randomized controlled trials of Rhubarb in the treatment of chronic renal failure in medical electronic databases (up to september 2021) were searched, and meta-analysis was carried out by revman 5.3 software. Results: A total of 2786 patients were included in 34 literatures, including 1474 cases in the treatment group and 1312 cases in the control group. The results of meta-analysis showed that Serum creatinine (SCR) [MD = 123.57, 95% Cl (111.59, 131.96)], Blood urea nitrogen (BUN) [MD = -3.26, 95% Cl (- 4.22, - 2.31)], Creatinine clearance rate (CCR) [MD = 3.95, 95% Cl (- 0.03, 7.93)], Hemoglobin (Hb) [MD = 7.70, 95% Cl (- 0.18, 15.58)] and Uric acid (UA) [MD = - 42.79, 95% CI (- 66.29, -19.29)].The total effective rate of improving symptoms and signs in CRF patients [Peto or = 4.14, 95% Cl (3.32, 5.16)]. Conclusion: Treatment with Rhubarb appears to have benefits in CRF patients.Compared with the control group, Rhubarb alone or traditional Chinese medicine compound containing Rhubarb can significantly reduce SCR, BUN and UA, increase CCR, and improve the total effective rate of symptoms and signs. However, there is no evidence that Rhubarb is more effective than the control group in increasing Hb. In addition, due to the low quality of research methodology in the included literature, it is necessary to further study high-quality literature to evaluate its efficacy and safety.